2018
DOI: 10.3389/fimmu.2018.01924
|View full text |Cite
|
Sign up to set email alerts
|

T Cells That Help B Cells in Chronically Inflamed Tissues

Abstract: Chronically inflamed tissues commonly accrue lymphocyte aggregates that facilitate local T cell-B cell interactions. These aggregates can range from small, loosely arranged lymphocyte clusters to large, organized ectopic lymphoid structures. In some cases, ectopic lymphoid structures develop germinal centers that house prototypical T follicular helper (Tfh) cells with high expression of Bcl6, CXCR5, PD-1, and ICOS. However, in many chronically inflamed tissues, the T cells that interact with B cells show subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
140
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(145 citation statements)
references
References 128 publications
5
140
0
Order By: Relevance
“…In line with previous observations, effector Tfh GC (CXCR5 hi PD-1 hi ) were the major sources of IL-21 and IL-4 and were only present in tonsil (Dan et al, 2019;He et al, 2013;Heit et al, 2017;Locci et al, 2013). The presence of Tfh GC cells in tonsils suggested a probable ongoing immune response in this tissue (Baumjohann et al, 2013;Hansen et al, 2016;Havenar-Daughton et al, 2016), which was not surprising considering that tonsillectomy is often a therapeutic surgical solution for recurrent chronic viral and bacterial infections (Dan et al, 2019;Grivel and Margolis, 2009;Rao, 2018). We also showed that Tfh GC cells are enriched in CXCR3cells and produced little IFN-g (Ma et al, 2009;Ploquin et al, 2011).…”
Section: Discussionsupporting
confidence: 60%
“…In line with previous observations, effector Tfh GC (CXCR5 hi PD-1 hi ) were the major sources of IL-21 and IL-4 and were only present in tonsil (Dan et al, 2019;He et al, 2013;Heit et al, 2017;Locci et al, 2013). The presence of Tfh GC cells in tonsils suggested a probable ongoing immune response in this tissue (Baumjohann et al, 2013;Hansen et al, 2016;Havenar-Daughton et al, 2016), which was not surprising considering that tonsillectomy is often a therapeutic surgical solution for recurrent chronic viral and bacterial infections (Dan et al, 2019;Grivel and Margolis, 2009;Rao, 2018). We also showed that Tfh GC cells are enriched in CXCR3cells and produced little IFN-g (Ma et al, 2009;Ploquin et al, 2011).…”
Section: Discussionsupporting
confidence: 60%
“…CXCL13 is a chemokine that recognizes CXCR5, a featured marker for Tfh cells . CXCL13 appears to be more specific marker for T‐B cell interaction and recruits CXCR5 + B cells and Tfh to lymphoid follicles . The production of IL‐21 by Tfh is important for B cell proliferation and differentiation into plasma cells .…”
Section: Discussionmentioning
confidence: 99%
“…T cell‐dependent production of antibodies to many different antigens requires T cell help. Follicular helper T cells (Tfh), with high expression of CXCR5, PD‐1 and ICOS, are critical in germinal centre (GC) reaction of B cells and determine the quality of humoral responses . Circulating Tfh (cTfh) cells in blood are also found, which are probably linked developmentally and functionally to GC Tfh .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Th 17 ) (1-4), signal and recruit B cells (e.g. Th 1 and Th 2 ) (5)(6)(7)(8)(9)(10)(11), and induce tolerance in the tissue microenvironment (e.g. T reg ) (12,13).…”
mentioning
confidence: 99%